A violência sexual infantil no judiciário: análise de uma amostra de sentenças judiciais - de Araújo, Nathalia Helena (2024)
Child sexual violence is defined as any sexual act committed by one or more adults against children and adolescents, leading to sexual stimulation of the victim and/or aggressor. Although the Judiciary has an important role in protecting the victim and holding the aggressor accountable, several problems in this instance have hindered the proper processing of judicial proceedings, making them time-consuming and resulting in costly effects on victims. The present study aimed to analyze the characteristics of a sample of court sentences involving child sexual violence in the state of São Paulo. A total of 10 sentences were selected between 2018 and 2022. The main results showed that longer sentences are characterized by more intrusive abusive acts, a greater number of aggressors belonging to the family nucleus and a greater amount of evidence mentioned compared to faster sentences. Possible relationships between the aforementioned characteristics and the slowness of the cases are discussed, highlighting the impacts of Law 13.431/2017 as an influence on the speed and reduction of the revictimization of children and adolescents, as well as the influence of the judicial system on the protection of victims.